Health Care Evaluation Using Computer Simulation Concepts, Methods, and Applications - Sobolev, Boris. (Springer US : Imprint: Springer, 2012)
Boris Sobolev · Victor Sanchez · Lisa Kuramoto Health Care Evaluation Using Computer Simulation Concepts, Methods, and Applications   Over the past decades, health services research has informed policy for improving health care delivery. Computer simulations have great potential to drive full scale improvement, yet the technology has rarely been used to evaluate proposed changes before they are implemented in health care systems. Health Care Evaluation Using Computer Simulation describes a new interdisciplinary approach, one that incorporates the simulation of health system operations into the paradigm of health services research. Beginning by reviewing the processes of health care evaluation and simulation experiments, the book presents a complete methodology for conducting simulation studies for evaluating policy alternatives. Unified Modeling Language and Statechart diagramming are introduced as a means for developing realistic requirements of discrete-event models and policies. And to clearly illustrate simulation modeling in context, an extended series of examples illustrates the use of simulations throughout a single department in a busy hospital. Chapters take the reader through each step of the methodology, featuring: • A comparison of approaches to constructing simulation models of health care systems. • An overview geared toward developing research questions. • A framework for determining model requirements and designing simulations. • Methods for evaluating simulation experiments at the cluster and individual levels. • Guidelines for clear reporting of simulation studies. • Examples of computer simulation in surgical services, from appointment booking to discharge planning.   As a research reference and a hands-on blueprint, Health Care Evaluation Using Computer Simulation breaks innovative new ground for researchers and graduate students in health services research and health care management.   Over the past decades, health services research has informed policy for improving health care delivery. Computer simulations have great potential to drive full scale improvement, yet the technology has rarely been used to evaluate proposed changes before they are implemented in health care systems. Health Care Evaluation Using Computer Simulation describes a new interdisciplinary approach, one that incorporates the simulation of health system operations into the paradigm of health services research. Beginning by reviewing the processes of health care evaluation and simulation experiments, the book presents a complete methodology for conducting simulation studies for evaluating policy alternatives. Unified Modeling Language and Statechart diagramming are introduced as a means for developing realistic requirements of discrete-event models and policies. And to clearly illustrate simulation modeling in context, an extended series of examples illustrates the use of simulations throughout a single department in a busy hospital. Chapters take the reader through each step of the methodology, featuring: • A comparison of approaches to constructing simulation models of health care systems. • An overview geared toward developing research questions. • A framework for determining model requirements and designing simulations. • Methods for evaluating simulation experiments at the cluster and individual levels. • Guidelines for clear reporting of simulation studies. • Examples of computer simulation in surgical services, from appointment booking to discharge planning.   As a research reference and a hands-on blueprint, Health Care Evaluation Using Computer Simulation breaks innovative new ground for researchers and graduate students in health services research and health care management.